Conditional impact of facebook as an information source on political opinions: the case of political reform in Hong Kong. Issue 3 (2nd September 2017) - Lee, Francis L. F.; Lee, Paul S. N.; So, Clement YK; Leung, Louis; Chan, Michael Cheming
ABSTRACT: This study is interested in the impact of Facebook as a source for political information on public opinion during political controversies. In a society where the mainstream media are under heavy influence by the dominant power and yet Internet communication is largely open and free, social media may become particularly important for the transmission of critical information and viewpoints. The social media information environment may exhibit an overall 'anti-establishment bias.' However, the impact of social media should vary across individuals depending on the extent and character of user selectivity. Analysis of data collected during the political reform debate in Hong Kong ( N = 3, 246) show that reliance on Facebook as an information source relates negatively to support for the government's reform proposal. But the relationship is strongest for people without a strong political orientation and people who do not name any newspapers as their main information source. General theoretical implications of the findings are discussed.